Rosa Campusano: patriota comprometida vista por la tradición de Palma y el historiador Germán Leguía - Mera Ávalos, Arnaldo (2018)
From the review of the tradition Rosa Campusano, “La Protectora” we will be able to reconstruct her participation in the work of propaganda and dissemination of the patriotic cause before and after the arrival of the Liberation Expedition of General San Martín in 1820 consulting the work of the Outstanding historian German Leguía and Martínez. Finally we will see how the new state constituted and denominated Protectorate decorated by this work in 1822 and the opinions expressed by don Ricardo Palma in this respect.